Surface Complexation Model Parameters for Goethite (α-FeOOH) - Lumsdon, David O.; Evans, Leslie J. (Journal of colloid and interface science, 1994)
Potentiometric titration studies on a pristine goethite suspension (α-FeOOH) have suggested alternative surface complexation model (SCM) parameters to those currently in use. It is proposed that the intrinsic surface acidity constants pKinta1 and pKinta2 should generally be higher than usually reported and the inner-layer capacitance in the region of 0.4-0.8 F m-2 for ionic strengths of 10-3-10-1M. The study demonstrates that some surface complexation model (SCM) parameters may be incorrect due to an experimental artifact, though they give good simulations of experimental data. This may be due to the success of least-squares fitting programs such as FITEQL at finding model parameters to describe experimental data sets. Previous studies have shown that goethite (α-FeOOH) suspensions purged with CO2-free N2(g) for up to two months have measured points of zero net protonic charge (PZNPC) in the range 9.0-9.3, which is close to a theoretical value of 9.4. However, most surface complexation modelsparameters, such as the two intrinsic surface acidity constants pKinta1 and pKinta2 and the inner layer capacitance κ1, have been determined from data sets in which the PZNPC was in the range 7.35-8.65. This study reports a set of surface complexation model parameters determined from potentiometric titration data obtained from goethite purged with CO2-free N2(g) for 2 months. Parameters were calculated using the computer program FITEQL within the context of three commonly used models, the diffuse double layer model, the constant capacitance model, and the triple layer model. The values of pKinta1 and pKinta2 found in this study were larger than previously reported values. In addition, the values of κ1 in the range 0.4-0.8 F m-2 were necessary to explain the data for ionic strengths in the range 10-3 to 10-1M; these values of k1, are lower than those currently in use. These revised parameters are consistent with the removal of a carbonate surface complex from the goethite, and suggest that artifacts have been introduced into many previously calculated surface complexation parameters. This raises questions on the methodology to be used to obtain titration data for determination of SCM parameters.